First year students' perceptions of excellent teachers - Cheah, Catherine Ming Ming (2007)
The purpose of this study is to examine the characteristic of a excellent lecturer as perceived by the first year students of Malay Woman Training Institute the similarities and differences in the responses based on education level. Knowing what characteristics are correlated with excellence in teaching is important because it provides both pre-service and in-service teachers with an opportunity to evaluate their own teaching, receive feedback from students, and improve teaching. Also, this knowledge aids teacher preparation programs in designing their courses and in recruiting the best candidates for teaching. This will help the Teacher Education Division in modifying the curriculum to enhancing specific skills that a teacher must possess. Two distinct samples were involved in this study: For the (5-point) Likert scale, data will be collected from a group of 56 post graduate students from local university and 205 O' level school leavers from Malay Women Teachers' Institute in Malacca. Data analysis using SPSS version 14 through comparing means frequency, percentage, t-test and One-Way ANOVA. The findings of this study indicate that good leader is an important characteristic that contributes to excellent teachers. More than 90% of the students agree that the teaching skills such as motivation, learning environment, facilitating learning, instructional approach and enhancement of student learning with technology should be present in an excellent teacher. .The comparison of the two means shows that students agreed that personal traits are more important than teaching skills in making an excellent teacher. There is no significant difference in the perceptions of excellent teachers between postgraduates and undergraduates students. The findings indicate that what matters most is employing a variety of teaching styles, positive attitude, establish a closer rapport with student can provide a better and conducive environment for learning. Lecturers must be more open to criticism, suggestions and constructive comments in other to change and adjust their personal traits to be a better person.